Diáspora africana na Paraíba do Norte: trabalho, tráfico e sociabilidade na primeira metade do século XIX - Guimarães, Matheus Silveira (2015)
The main subject of this work is the African population of slaves and free people who lived in Paraíba in the first half of the 19th century. For many decades, historiography has denied, omitted or minimized the participation of African people in the historical process. However, the presence of men and women who came from Africa was constant in this province. Our main goal is to understand how the African population was introduced in Paraíba (a peripheral region in the Atlantic trade of slaves) and how they lived there. In order to achieve it, we have outlined a historiographical route to identify the gaps in a given historical culture. By making usage of the theoretical and methodological assumptions of Marxist Social History, we have made a critique of this portion of historiography that denied the participation of black populations and African populations in particular in the history of the province. Next, by using a variety of sources such as reports and official mail correspondence of governors and presidents of Paraíba, inventories and wills, requests of release, baptism records, manumission and many others, we have managed to comprehend further on the matters issued, approaching social and economic aspects of the region, indicating which were the main routes of importation and what was the everyday-life of African people. We have come to realise that Paraíba was inserted in the Atlantic trade of slaves indirectly which had a complementary character to this slave-holding society. Therefore the quantity of slaves who came from Africa was inferior to the ones sent to other locations such as Recife, Salvador and Rio de Janeiro. This factor marked certain specificities in the life of these African people. However the fundamental practise of slavery remained: violence.